When Your Pronominal Marking Matters during a Pandemic: Shawi Pronominals and COVID-19 Interventions - Luis Miguel Rojas-Berscia (Languages, 2024)
In this communication, I focus on Shawi forms of address used in Peruvian State posters during the COVID-19 pandemic. The COVID-19 pandemic took a heavy toll on the Peruvian Indigenous population. A recent study showed that Indigenous people had 3.18 times the risk of infection and 0.4 times the mortality risk of the general population in Peru. The Shawi have not been included among the most heavily affected. A preliminary descriptive and critical account of Peruvian State posters whereby languages such as Shawi and other Peruvian Indigenous languages (Awajun, Ashaninka, different varieties of Quechua, Shipibo, etc.) have been used to prevent the spread of COVID-19 is provided. Shawi seems to be the only language of the sample where information has been framed using first-person inclusive forms. This appears to have led to enhanced communal engagement in the suggested health-related practices. Additionally, opinions on the issue from local stakeholders are briefly discussed. While the results are derived solely from preliminary observations, my findings could serve as a basis for enhancing health communication strategies in other Indigenous contexts, utilizing linguistically informed intercultural approaches.